Coincidence study of double electron emission associated with K-shell photoionization of C60 - Korica, Sanja Lj.; Reinkoester, Axel; Becker, Uwe (Vojnotehnički glasnik / Military Technical Courier, 2018)
The (multiple) photoionization and subsequent fragmentation of the C60 molecule was studied with the synchrotron radiation after removing electrons from the inner K-shell. Our intention was especially focused on the dynamics of the subsequent fragmentation. In addition to ’normal’ (non-coincident) electron and ion time-of-flight spectroscopy, we investigated this topic with the help of an electron–electron-coincidence measurement. Our experiment shows that in these processes Cq+60 ions with charge states up to 3+ and several smaller Cq+60-2m fragments are formed. In addition, the broad peak besides the C(1s) line, usually referred to as the ’plasmon’ peak, has been observed.